Intermittent Fever, Progressive Weight Gain, and Personality Changes in a Five-Year-Old Girl: Unusual Paraneoplastic Syndrome due to Presacral Ganglioneuroma - Chao Yang; Chang-chun Li; Jun Zhang; Xiang-ru Kong; Zhenzhen Zhao; Xiao-bin Deng; Liang Peng; Shan Wang (Case Reports in Endocrinology)
Ganglioneuromas are rare tumors in the neuroblastoma group. Paraneoplastic syndrome (PNS) due to presacral ganglioneuromas was hardly reported in previous literature. Here, we reported that a case of a 5-year-old girl with a presacral ganglioneuroma presented with PNS, who presented with intermittent fever, progressive weight gain, and personality changes. Our report revealed intermittent fever, progressive weight gain, and personality changes may represent rare paraneoplastic syndromes in ganglioneuromas.